FEM analysis with shell element model in order to design support structure for PV system - Yasuhiro MAEDA (The Japan Society of Mechanical Engineers, 2020)
In recent years, accidents have frequently occurred under the rapid spread of the photovoltaic power generation system in Japan. In order to make the design procedure for the support structure safety, in the previous studies, the authors have compared the experimental results with the FEM analytical results by using the beam element model. The results show that it can evaluate the deformation of the support structure qualitatively, determine the buckling member, and calculate the buckling load. However, it was not easy to quantitatively evaluate the deformation of the support structure in the analysis with the beam element model. In this study, in order to do quantitative evaluation for the deformation of the support structure, FEM analysis was performed by using the shell element model and through comparing experimental results with analytical results. From these results, it is found that the buckling member was determined and its bucking load could be calculated precisely. Furthermore, in order to examine the deformation and fracture process of the angle members, we conducted elastoplastic FEM analysis for the angle member. We will clarify the deformation behavior of the angle steel member until the buckling, and show new knowledge in the destruction of the whole of the support structure.